2021
DOI: 10.1002/smll.202101837
|View full text |Cite
|
Sign up to set email alerts
|

Red Phosphorus Decorated TiO2 Nanorod Mediated Photodynamic and Photothermal Therapy for Renal Cell Carcinoma

Abstract: most frequent among females (the ratio between affected men and women is 2:1). [1,2] Approximately 270 000 new cases of RCC and 116 000 RCC-related deaths are reported worldwide per year. [3] Among the reported patients, clear cell RCC (ccRCC) cases account for 70-80%. [4] The cure rate of advanced ccRCC patients with a 5-year survival rate is as low as 11.7%, so efficient treatment is necessary. [5,6] Surgery is the most common treatment for ccRCC. However, with the high invasiveness and high resistance to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 62 publications
0
35
0
Order By: Relevance
“…There is a large demand for new treatments for RCC. A facilely prepared core–shell structured TiO 2 @red phosphorus nanorods (TiO 2 @RP NRs) that can effectively mediate the combined PDT and PTT for clear cell RCC (ccRCC) was reported [ 93 ]. Red phosphorus (RP), a new class of biophotocatalysts, displaying great absorption of NIR [ 156 ], was deposited onto the TiO 2 NR surface to extend the absorption range of TiO 2 @RP NRs to NIR.…”
Section: The Latest Advances In Preclinical Researches Of Pdt/sdt For...mentioning
confidence: 99%
“…There is a large demand for new treatments for RCC. A facilely prepared core–shell structured TiO 2 @red phosphorus nanorods (TiO 2 @RP NRs) that can effectively mediate the combined PDT and PTT for clear cell RCC (ccRCC) was reported [ 93 ]. Red phosphorus (RP), a new class of biophotocatalysts, displaying great absorption of NIR [ 156 ], was deposited onto the TiO 2 NR surface to extend the absorption range of TiO 2 @RP NRs to NIR.…”
Section: The Latest Advances In Preclinical Researches Of Pdt/sdt For...mentioning
confidence: 99%
“…The oxygen vacancy engineering provides a new strategy for constructing multifunctional nanomaterial and achieving efficient synergistic therapy. Thus, some oxygen vacancy-engineered nanomaterials have been developed to efficiently combine PDT and PTT to improve the phototherapeutic efficacy against tumor ( Sun et al, 2019 ; Wang X. et al, 2019 ; Maleki et al, 2021 ; Yang et al, 2021 ). For example, Xu et al ( Yang et al, 2021 ) synthesized the core−shelled TiO 2 @red phosphorus nanorods (TiO 2 @RP NRs) as a nanophotosensitizer for synergetic PDT and PTT, through the vaporization-deposition (VP) method.…”
Section: Vacancy Defective Nanomaterials-enhanced Phototherapy and Mu...mentioning
confidence: 99%
“…Thus, some oxygen vacancy-engineered nanomaterials have been developed to efficiently combine PDT and PTT to improve the phototherapeutic efficacy against tumor ( Sun et al, 2019 ; Wang X. et al, 2019 ; Maleki et al, 2021 ; Yang et al, 2021 ). For example, Xu et al ( Yang et al, 2021 ) synthesized the core−shelled TiO 2 @red phosphorus nanorods (TiO 2 @RP NRs) as a nanophotosensitizer for synergetic PDT and PTT, through the vaporization-deposition (VP) method. It can be observed that more oxygen vacancies were created in nanosized TiO 2 core after the vaporization-deposition, which led to a significantly enhanced NIR absorption in the range of 640–1,100 nm.…”
Section: Vacancy Defective Nanomaterials-enhanced Phototherapy and Mu...mentioning
confidence: 99%
“…In addition, photodynamic and photothermal therapy are usually applied in combination due to their synergistic tumor killing effect (Figure 2). Photothermal therapy generates heat locally can not only ablate tumor cells, but also accelerate blood circulation and accumulate oxygen in the tumor's hypoxic microenvironment to provide suitable conditions for photodynamic therapy (Yang et al, 2021). Guan et al prepared covalent organic framework nanoparticles with a particle size of ~140 nm that co-loaded the photosensitizer porphyrin and the photothermal agent naphthalocyanine.…”
Section: Nanomaterials Used In Photothermal Therapy and Photodynamic ...mentioning
confidence: 99%
“…Yang et al synthesized TiO 2 @RP nanorods with red phosphorus (RP) as the shell and TiO 2 as the core. After being irradiated with 808 nm NIR light for 5 min, the nanorods can reach 39.3-44.1 °C and induce the production of 1 O 2 , effectively killing cancer cells in deep tissues of renal cell carcinoma (Yang et al, 2021).…”
Section: Nanomaterials Used In Photothermal Therapy and Photodynamic ...mentioning
confidence: 99%